2015
DOI: 10.1016/j.chb.2014.12.057
|View full text |Cite
|
Sign up to set email alerts
|

The internet and young people with Additional Support Needs (ASN): Risk and safety

Abstract: The aim of this study was to investigate the understanding of online risks by young people with Additional Support Needs and this group's ability to manage these risks.Six focus groups with 36 young people (13-18) were run in local schools. Discussions were recorded, transcribed and analysed using Framework Analysis. Two themes were identified 'Identity and Connectedness' and 'Issues relating to Risk'. The theme 'Issues relating to Risk' is presented in the current article. Results showed that young people wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 36 publications
2
26
0
2
Order By: Relevance
“…Frente a las oportunidades y ventajas asociadas, el acceso generalizado a las TICS, de forma paralela se ha generado un clima de preocupación social en torno a los peligros a los que se exponen los/las adolescentes. Diversos trabajos advierten de las posibles consecuencias negativas derivadas de un mal uso de la Red y las TICS (Bannon et al, 2015;Rial et al, 2014b) y es precisamente en este marco de prácticas virtuales "peligrosas" donde surgen las conductas de sexting.…”
Section: Introductionunclassified
“…Frente a las oportunidades y ventajas asociadas, el acceso generalizado a las TICS, de forma paralela se ha generado un clima de preocupación social en torno a los peligros a los que se exponen los/las adolescentes. Diversos trabajos advierten de las posibles consecuencias negativas derivadas de un mal uso de la Red y las TICS (Bannon et al, 2015;Rial et al, 2014b) y es precisamente en este marco de prácticas virtuales "peligrosas" donde surgen las conductas de sexting.…”
Section: Introductionunclassified
“…2015). Bannon et al (2015) reports the results of a focus group study conducted with 36 young people described as having 'additional support needs' designed to investigate their understanding of online risks. The results revealed that the young people were aware of a range of risks and had developed some strategies to manage these which often involved asking for support from adults or peers.…”
Section: Perceptions Of Internet Riskmentioning
confidence: 99%
“…There is evidence to show that some people with IDD may not necessarily be unaware of the risks of Internet use (Löfgren-Mårtenson, 2008;Bannon, McGlynn, McKenzie, & Quayle. 2015).…”
Section: Perceptions Of Internet Riskmentioning
confidence: 99%
“…This number is still increasing, and even children between the ages of 5 and 8 have a local internet connection. Society has given more attention to protecting adolescents and children from external physical hazards, and they have not paid attention to technological interaction [2], [4] and [5]. Computer and artificial intelligence experts say there is an emotional connection between teens and electronic games around the world, as they seem to know in their depths that they are the computer generation [15].…”
Section: A Adolescent Behavior On the Internetmentioning
confidence: 99%